Management of acute pediatric pain in the emergency department. Issue 3 (June 2016) - Ruest, Stephanie; Anderson, Angela
Abstract : Purpose of review: This article provides a summary of recommendations for the multimodal and multidisciplinary approach to acute pediatric pain management and highlights recent research on this topic. Recent findings: Recent literature has focused on updating recommendations for the use of various analgesics in the pediatric population. While codeine is no longer recommended due to increasing evidence of adverse effects, the more liberal use of intranasal fentanyl is now encouraged because of the ease of administration and rapid delivery. The evidence base for the use of ultrasound-guided regional nerve blocks by qualified providers in the acute pediatric pain setting continues to grow. Summary: The pediatric emergency medicine provider should be able to assess pain and develop individualized pain plans by utilizing a range of nonpharmacologic and pharmacologic strategies. Knowledge of the most recent literature and changes in recommendations for various pain medications is essential.